THE THE MEDIATING ROLE OF WORK MOTIVATION ON THE INFLUENCE OF CAREER DEVELOPMENT ON STARTUP EMPLOYEE PERFORMANCE IN INDONESIA IN THE ERA OF INDUSTRIAL REVOLUTION 4.0 - Pynasthika, Qeisha Amaliah; Andriansyah; Lumbanraja, Prihatin (Strategic Management Business Journal, 2023)
The study's outcomes aim to provide solutions by emphasizing work motivation as a mediating factor in the correlation between career development and employee performance. The data used in this study are primary data obtained from the completion  of questionnaires by 50 respondents in emp`loyee start up. Data  analysis tool used is SmartPLS Windows 3 software. Based on the study results, it can be concluded that 1) the first hypothesis (H1) was accepted if the P-Value was less than 0.010 < 0.05 and original sample 0.331. It may be inferred from this research that career development positive and influences employee performance 2) the second hypothesis (H2) was accepted if the P-Value was less than 0.000 < 0.05 and original sample 0.675. It may be inferred from this research that work motivation positive and influence employee performance 3) Based on the study results, it can be concluded that the third hypothesis (H3)  was accepted if the P-Value was less than 0.010 < 0.05 and original sample 0.440. It may be inferred from this research that work motivation mediating influence career development on employee performance. JEL Classification: M21, M31